Stochastic process drives the dissimilarity in biodiversity patterns between Pinus kwangtungensis coniferous forest and evergreen deciduous broad-leaved mixed forest in karst area - Fan, Xingying; Meng, Longchenxi; Wang, Yeheng; Zang, Lipeng (PeerJ, 2024)
Pinus kwangtungensis is an endangered evergreen conifer tree species, and its in situ conservation has been considered one of the most critical issues. However, relative protection is limited by the lack of understanding of its community structure and underlying assembly processes. To study how the species diversity and assembly processes of Pinus kwangtungensis coniferous forest (CF) differed with regional climax community, this study established a series forest dynamic plots both in CF and evergreen deciduous broadleaved mixed forest (EDBM). By performing comparison analysis and PER-SIMPER approaches, we quantified the differences in species diversity and community assembly rules. The results showed that the species α-diversity of CF differed greatly from the EDBM both in species richness and evenness. In addition, the stochastic process acted a more important role in determining species composition, indicating the uncertainty in presence of species. The soil phosphorus and changeable calcium content were the main factors driving the differences in biodiversity, which the importance of soil nutrient factors in driving species composition. Our study highlighted that we should consider the community structure and ecological process when conducting conservation of Pinus kwangtungensis.
Keywords: Community assembly rules; Pinus kwangtungensis; Species abundance distribution; Karst forest